Perilaku Mencari Peluang, Kapabilitas Inovasi dan Penciptaan Nilai UKM Kerajinan - Paulus, Ardianus Laurens; Farida, F. Anif (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Opportunity-seeking behaviour is a function of a company's entrepreneurial strategy. Through seeking opportunities, companies are expected to develop competence in identifying opportunities to encourage innovation and create new values in business activities. This study examines the influence of opportunity-seeking behaviour on innovation capability and value creation in craft SMEs in the Madiun area. The research method uses surveys with online and offline questionnaires to further explore craft SMEs' perceptions regarding opportunity-seeking behaviour, innovation capability and value creation. Data analysis using Smart PLS version 3.0. The results show that opportunity-seeking behaviour and innovation capability significantly and positively affect value creation. The existence of the company's opportunity-seeking behavior can increase the ability to transform existing knowledge into an innovation and make the company more effective in creating value. In addition, innovation is considered a strong predictor of creating new value that is beneficial to improving company performance The mediating role of innovation capability plays a role as a mediator and is supported in this study.